Cocaine using patient who presents with dyspnoea - RA Castro Jiménez; I García Alcaide; N Pascual Martínez
ABSTRACT We present the case of a 17-year-old male patient with a history of cocaine use who consulted for chest pain and dyspnoea. A pneumomediastinum is defined as the irruption of air in the mediastinal space, and is associated with different causes, including addiction to inhaled drugs. It occurs in people with predisposing factors and the presence of precipitating factors such as consumption of inhaled drugs. X-ray and computed tomography of the thorax are very useful tools in guiding the diagnosis. The low incidence of this pathology represents a difficult diagnosis for the doctor, although in some characteristic work environments a high level of suspicion is necessary.